Mixed Research Paradigm: A Parsimonious Approach! - Joshi, S (Journal of Institute of Medicine Nepal, 2013)
DOI: http://dx.doi.org/10.2126/joim.v35i1.8904 Journal of Institute of Medicine, April, 2013; 35:78-81